Optimization of nonedible oil extraction from Cassia javanica seeds. Issue 11 (3rd June 2017) - Murugesan, Karthikeyan; Sahadevan, Renganathan
ABSTRACT: The current scenario in many of the countries in the world is energy importers. The largest demand occurs in energy sources especially crude products.Biodiesel is a nontoxic and decomposed organic matter. It is gathered from various sources such as animal fats, vegetable oil, and algae. In this work, the modified Soxhlet device is used as a promising new source to extract the bio-oil from Cassia javanica seeds. Throughout the study of extraction time will carried over by 3.5 hours for the production of bio-oil using hexane at 68 °C, by the time of 3.5 hours.The parameters of physical and chemical properties and fuel properties are analyzed by AOCS and ASTM standard methods.